2019
DOI: 10.1021/acsami.9b17143
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regulation of Neurons, Glial Cells, and Neural Stem/Precursor Cells by Poly(allylguanidine)-Coated Surfaces

Abstract: Poly(allylguanidine) (PAG) was synthesized and characterized as a polycationic coating material for culturing neurons, glial cells, and neural stem/precursor cells (NSPCs) to apply PAG for neural tissue engineering. For comparison, poly-D-lysine (PDL), the golden benchmark of the neuron cell culture system, was also used in this study. When PAG was subjected to a mixed culture of neurons and glial cells, cell adhesion and neurite extension of neuronal cells were clearly observed but only few glial cells could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Examination of the culture via phase-contrast imaging before fixation showed a similar sparse distribution of surviving neurons, indicating that the few cells present after immunolabeling are not due to cellular detachment during the fixation, washing and labeling steps, but rather reflect the inability of cells to adhere and survive on a minimally coated glass surface. Certain polycationic surface coatings may impact the proliferation or differentiation of either neurons or glia ( Ji et al, 2019 ). However, few S100β positive glial cell bodies were present in these 7 DIV cultures, and the few cells detected did not appear to be significantly affected by the type of substrate used (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of the culture via phase-contrast imaging before fixation showed a similar sparse distribution of surviving neurons, indicating that the few cells present after immunolabeling are not due to cellular detachment during the fixation, washing and labeling steps, but rather reflect the inability of cells to adhere and survive on a minimally coated glass surface. Certain polycationic surface coatings may impact the proliferation or differentiation of either neurons or glia ( Ji et al, 2019 ). However, few S100β positive glial cell bodies were present in these 7 DIV cultures, and the few cells detected did not appear to be significantly affected by the type of substrate used (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…While the coatings initially used for neuronal cultures were either proteins or polypeptides, other synthetic/non-peptide cationic linear polymers have been investigated for their capacity to support neuronal adhesion and growth ( Ji et al, 2019 ; Lakard et al, 2005 ; Landry et al, 2018 ; Schmidt et al, 1997 ; Vancha et al, 2004 ). dPGA belongs to a class of purely synthetic highly branched polymers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various scaffolds used for growing nerve cells have been functionalized with bioactive molecules. [67,68] However, the effects of different scaffold surface modifications on nerve cell growth are not known. Nerve cell behavior can be regulated by the physicochemical properties of the modified scaffold surface, which would result in altered regeneration efficiency of the damaged peripheral nerve.…”
Section: Different Surface Modifications Of Scaffoldsmentioning
confidence: 99%
“…In addition, the guanidine group demonstrates fine affinity with the phosphate group where PAG could strongly contact the cell membrane to affect the cell fate. Furthermore, our previous study indicated that PAG promotes neural viability and induces neural stem/precursor cells (NSPCs) to differentiate into neurons . Nonetheless, the exact mechanism behind the anti-cancer effects of PAG is not well understood.…”
Section: Introductionmentioning
confidence: 99%